Expert review on usefulness of an integrated checklist-based mobile usability evaluation framework - Zulzalil, Hazura; Rahmat, Hazwani; Abd Ghani, Abdul Azim; Kamaruddin, Azrina (Bilingual Publishing Group, 2023)
Previous mobile usability studies are only pertinent in the context of ergonomics, physical user interface, and mobility aspects. In addition, much of the previous mobile usability conception was built on desktop computing measurements, such as desktop and web application checklists, or scarcely addressed the mobile user interface. Moreover, the studies focus mainly on interface features for desktop applications and do not reflect comprehensive mobile interface features such as navigation drawers and spinners. Therefore, conducting usability evaluation using conventional usability measurement would result in irrelevant results. In addition, the resulting works are tailored for usability testing, which requires highly skilled evaluators and usability specialists (e.g., usability testers and user experience designers), who are rarely integrated into a development team. The lack of expertise could lead to unreliable usability evaluations. This paper presents a review from industrial experts on a comprehensive and feasible usability evaluation framework developed in our previous work. The framework is dedicated to smartphone apps, which integrate evaluator skills and design concerns. However, there is no evidence of its usefulness in practice. Therefore, the usefulness of the framework measurement for evaluating apps' usability in the eyes of non-usability specialists is empirically assessed in this paper through an expert review. The expert review involved eleven industrial developers and was complemented by a semi-structured interview. The method is replicated in comparison with a framework from another study. The findings show that the formulated framework significantly outperformed the framework (p = 0.0286) from other studies with large effect sizes (r = 1.81) in terms of usefulness.